Peran Pendampingan Belajar Nahwu Dalam Meningkatkan Pengaruh Positif Minat Belajar Siswa - Novena Ade Fredyarini Soedjiwo; Kusjuniati Kusjuniati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The aim of the service is to provide solutions to problems found in the assisted locations, especially in nahwu learning activities at Madrasah Diniyah At-Taqwim. Assistance provided by seventh semester students at STAI Denpasar Bali to students in learning Arabic by studying Nahwu. The students learn Arabic to read the yellow book. In studying Arabic, students must be able to understand the meaning. Students at the Madrasah Diniyah At-Taqwim Islamic Boarding School are still weak in mastering Arabic, while these students are not interested in learning Arabic, because they have difficulty understanding. Students learn to read the yellow book traditionally by memorizing, while not all students are able to memorize. The service method in the role of nahwu learning assistance is the participatory action research method, starting with observation, planning, implementation and evaluation. Mentoring is carried out by empowering teachers according to their competencies and motivating and monitoring activities so that teachers and students can carry out the Nahwu learning process. The teacher is able to instruct and demonstrate in learning Nahwu using cooperative learning methods, so that he is able to show that students are interested in learning Nahwu in Arabic.